7(9x+-1)=64x-9-3

Simple and best practice solution for 7(9x+-1)=64x-9-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(9x+-1)=64x-9-3 equation:



7(9x+-1)=64x-9-3
We move all terms to the left:
7(9x+-1)-(64x-9-3)=0
We add all the numbers together, and all the variables
7(9x-1)-(64x-12)=0
We multiply parentheses
63x-(64x-12)-7=0
We get rid of parentheses
63x-64x+12-7=0
We add all the numbers together, and all the variables
-1x+5=0
We move all terms containing x to the left, all other terms to the right
-x=-5
x=-5/-1
x=+5

See similar equations:

| 0.4*x+x=100 | | 11(b-18)-6(2b+1)=4(-b+9) | | 5q+3=20 | | 14-5x+5-x+9-2x=180 | | 3.5x3x=28 | | 6x^{2}-21=33 | | 11w+19=19 | | 2x-(5/9)=7-(4/3)x | | x+3x9=45 | | 51n=70 | | 4b+3=−9​ | | 3|2x+4|=4 | | 4x+25=3x+29 | | 1.520=7x+15x | | −24−81​ x=83​ x | | 2x+5/9=7-4/3x. | | O.2x+5=8 | | .2(x-4.5)+1.7=9.6 | | 90=-5(2+b) | | 5(2x+4)=(x+2) | | 3m-62=8 | | 7^(3x+4)=28 | | -x^2=7x-12 | | 6x+4+15-7x=0 | | 3^x-2=27^4x | | -489=-8(7x-1) | | 5v+1=5 | | 9p+4=96 | | 9x=7+15 | | 7=-10a-3 | | 14=3-4b | | 3/0.5=x/1.5 |

Equations solver categories